Optimization Of Integrated Management Model Of Tourism Industry On Culinary Business In Kenjeran Tourism Region Surabaya - R Agus Baktiono; Wahyudiono Wahyudiono; Eman Setiawan; Soebandi Soebandi (LPPM of NAROTAMA UNIVERSITY, 2018)
ABSTRACT This research was aimed at (1) improving local wisdom values in integrated management of tourism industry and Micro Small and Medium Enterprises (MSMEs) center and (2) making tourism industry and MSMEs of a particular region to be an independent economic power; by being able to provide factual contribution for prosperity of the society observed from the perspective of tourism region, tourism actors, market, infrastructure, and management development aspects. The results showed that the implementation of tourism region and infrastructure aspects on a culinary business was within the score range of 80 to 100% or said to be in a very good factual condition. This implied that the employment of tourism region and infrastructure aspects played significantly influential and important roles for the development of tourism region allocated for culinary businesses within the area of THP Kenjeran. Meanwhile, for the implementation of tourism actors and market aspects, it was indicated that the score range was between 15 and 35%, and the implementation of management development aspect was between the score range of 0 and 5%. In other words, the implementations of those aspects were said to be very low in real conditions, especially on the indicators of training, cooperation with stakeholders, and suitable management implementation related to the business. This meant that the employment of tourism actors, market, and management development aspects were not suitable and did not accommodate the management development of the tourism region for culinary businesses within the area of THP Kenjeran. Keywords : Optimization, Integrated Management Model